Appied Nuclear Physics-Advanced Ion Beam Materials Analysis at small Accelerators - Grötzschel, R.; Kreissig, U.; Neelmeijer, Ch. (HNPS Advances in Nuclear Physics, 2020)
The ossendorf Ion Beam Laboratory has been developed to an international large scale user facility in the field of ion beam physics and ion beam materials research. The laboratory operates a large number of modern experimental equipment at three MeV accelerators, three implanters, an ECR source and a FIB which together pro- vide almost all ions species in a wide energy range from a few hundred eV to a few ten MeV. Also IBAD and PHI devices were installed for various purposes. The re- search stations at the accelerators are supplemented by complementary techniques like TEM, SEM, AUGER, AFM etc., all contributing useful information to thin film investigations. In this paper a short overview of the laboratory is given and a few recent experiments and their results are shown. Rutherford Backscattering Spec- trometry ( RBS) and Elastic Recoil Detection Analysis (ERDA) are well established techniques for quantitative thin film. The advantage of these methods consists in the simple physics they are basing on, namely the stopping of energetic ions in matter and the binary scattering of at the Coulomb potential of atomic nuclei. The increasing importance of ultra-thin layers for novel technologies demands quantita- tive analysis techniques with a depth resolution of atomic monolayers, which can be obtained for RBS and ERDA by magnetic spectrometers only. The magnetic spec- trometers we have installed at the 3 MV Tandetron and at the 5 MV tandem are described , recent applications are shown and a few problems to achieve high depth resolution will be discussed. Heavy ion detectors as Bragg IC, dE-Erest-telescopes and ToF spectrometers, developed for nuclear physics experiments, are now applied for ERDA, providing an efficient analysis of thin films containing light elements. The lateral position resolution of such detectors enables kinematic corrections and allows large solid angles. Thus by ERDA in situ studies during surface modification processes are possible like in the case of the nitridation of aluminum and stainless steel. At the external beam mainly objects of fine arts or of historical value are analysed. It will be shown, how the complementary application of PIXE, RBS and PIGE can help to detect the beginning corrosion of mediaeval glass objects.